SYNTHESIS AND CHARACTERIZATION OF MAGNETIC-HYDROXY APATITE COMPOSITE USINGONE SPOT COPRECIPITATION METHOD - Mujamilah Mujamilah; Ahmad Furqon Syidik; Grace Tj. Sulungbudi; Wildan z Lubis; Aloma Karo Karo (Jurnal Sains Materi Indonesia, 2017)
SYNTHESIS AND CHARACTERIZATION OF MAGNETIC-HYDROXY APATITE COMPOSITE USINGONE SPOT COPRECIPITATION METHOD. Nanocomposite of magnetic-hydroxyapatite (MHAP) has the potential to be developed as a biocompatible-biodegradable material for bone cancer diagnosis and therapy. In this study, such composite materials have been successfully synthesized by one-spot coprecipitation method and ultrasonic dispersion. The mass ratio between magnetic and hydroxyapatite fraction were varied to 30:70 (K30), 40:60 (K40) and 50:50 (K50). X-Ray Diffractometer, Transmission Electron Microscope, Fourier Transform-Infrared Spectrometer and Vibrating Sample Magnetometer were used for characterizing the properties of MHAP composite. X-Ray Diffraction pattern reveals the presence of magnetic and HAP phases, confirm the establishment of MHAP composite system. TEM image and FT-IR spectra shows the spherical morphology of magnetic nanoparticles with a size of ~ 10 nm entrapped within HAP nanorod structure without any chemical bonding between the two phase.With such physical composite mechanismand higher energy induce by ultrasonic dispersion process, magnetic fraction of even 50% mass fraction could still be loaded into HAP matrix and provide maximum magnetisation value of 34.6 emu/g. This magnetization value is higher than the result of another study of MHAP synthesis, giving better prospect for bone cancer diagnosis and therapy.